Wireless sensor networks mapping and deployment in tropical precision farming - Azizi, Harun; Ali Yeon, Md Shakaff, Prof. Dr.; Ammar, Zakaria; Latifah Munirah, Kamarudin; Mahmad, Nor Jaafar; Ndzi, David L. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://www.ieee.org/